Ultrasound-triggered delivery of iproplatin from microbubble-conjugated liposomes - Browning, R; Thomas, N; Marsh, LK; Tear, LR; Owen, J; Stride, E; Farrer, NJ (Wiley, 2021)
The PtIV prodrug iproplatin has been actively loaded into liposomes using a calcium acetate gradient, achieving a 3-fold enhancement in drug concentration compared to passive loading strategies. A strain-promoted cycloaddition reaction (azide- dibenzocyclooctyne) was used to attach iproplatin-loaded liposomes L(Pt) to gas-filled microbubbles (M), forming an ultrasound-responsive drug delivery vehicle [M−L(Pt)]. Ultrasound-triggered release of iproplatin from the microbubble-liposome construct was evaluated in cellulo. Breast cancer (MCF-7) cells treated with both free iproplatin and iproplatin-loaded liposome−microbubbles [M−L(Pt)] demonstrated an increase in platinum concentration when exposed to ultrasound. No appreciable platinum uptake was observed in MCF-7 cells following treatment with L(Pt) only or L(Pt)+ultrasound, suggesting that microbubble-mediated ultrasonic release of platinum-based drugs from liposomal carriers enables greater control over drug delivery.